Anaerobic-aerobic treatment of swine wastewater in uasb and batch reactors in series - Urbinati,Estevão (2014)
In this work it was evaluated the performance of two systems of swine wastewater treatment consisting of two-stage upflow anaerobic sludge blanket (UASB) reactors, with and without post-treatment in sequencing batch reactor (SBR), fed continuously, with aerobic phase. The UASB reactors in the first stage had 908 L in the sets I and II, and in the second stage 350 and 188 L, respectively. In the set II the post-treatment was performed in a SBR of 3,000 L. The hydraulic detention times in the anaerobic treatment systems were 100, 75 and 58 h in the set I; 87, 65 and 51 h in the set II; and 240 and 180 h in the SBR. The volumetric organic load applied in the first stage UASB reactors ranged from 6.9 to 12.6 g total COD (L d)-1 in the set I and 7.5 to 9.8 g total COD (L d)-1 in the set II. The average removal efficiencies of total COD, total phosphorus (Ptotal), and Kjeldahl and organic nitrogen (KN and Norg) in the anaerobic treatment systems were similar and reached maximum values of 97%, 64%, 68%, and 98%. In the SBR, the removal efficiencies of total COD and thermotolerant coliforms were up to 62 and 92% resulting, respectively, in effluent concentrations of 135 mg L-1 and 2x10(4)MPN (100 mL)-1. For Ptotal, total nitrogen (TN) and Norg, the average removal efficiencies in the SBR were up to 58, 25 and 73%, respectively.